Effect of tufting technique on sound insulation of multi-layer glass woven fabrics. (25th September 2020) - Shen, Hao; Yang, Yong; Wang, Peng; Hong, Yan; Legrand, Xavier; Yang, Xuhong; Wu, Jiankun
Abstract: A new idea to influence the sound insulation property of multi-layered woven fabric by the embedded tufting yarns is presented in this paper. The effect of layer number, layer orientation, tufting density and tufting pattern is investigated respectively, in the basis of sound transmission loss (STL) analysis measured by an impedance tube. The experimental results show that the sound insulation can be enhanced by increasing the number of layers or maintaining the same lay-up orientations. Moreover, the effect of tufting yarns on sound insulation is more sensitive in the low-middle frequency range and relatively more complicated. The obtained results can be applied in the part design, the preform engineering, and the positioning of tufting process.